Colloidal liquid crystals in square confinement: isotropic, nematic and smectic phases. (21st December 2016) - Cortes, Louis B G; Gao, Yongxiang; Dullens, Roel P A; Aarts, Dirk G A L
Abstract: We report on the confinement of colloidal liquid crystals in three dimensional chambers with a square footprint. To this end we use colloidal silica rods and exploit their relatively large density difference with respect to the dispersing solvent to study isotropic, nematic and smectic phases confined into a single chamber. Combining laser scanning confocal microscopy and soft-lithography techniques enables us to characterize the configurations down to the single particle level. We will focus on the smectic phase and compare to recent theories and simulations.